2017
DOI: 10.1111/area.12333
|View full text |Cite
|
Sign up to set email alerts
|

Linking online social proximity and workplace location: social enterprise employees in British Columbia

Abstract: Online professional networks have the potential to expedite and expand the success of corporations and, especially, socially oriented enterprises – such as non‐governmental organisations (NGOs) and social enterprises, which are businesses owned and operated by a non‐profit. Research to date has not examined the extent and composition of online professional social networks among social enterprise employees nor their inter‐relationships. Specifically, the link between individual connectivity and physical workpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Huang and Cox (2016) observed that engagement through social media platforms effectively allow us to alleviate poverty among disadvantaged people in Taiwan. Building upon a case study from Canada, Keane et al (2017) found that senior staff of SEs use LinkedIn to communicate across space and access updated knowledge sources. LinkedIn communication networks also offer communities quick access to jobs (Ellison et al, 2007).…”
Section: Fig2 Abstract' Co-occurrence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Huang and Cox (2016) observed that engagement through social media platforms effectively allow us to alleviate poverty among disadvantaged people in Taiwan. Building upon a case study from Canada, Keane et al (2017) found that senior staff of SEs use LinkedIn to communicate across space and access updated knowledge sources. LinkedIn communication networks also offer communities quick access to jobs (Ellison et al, 2007).…”
Section: Fig2 Abstract' Co-occurrence Analysismentioning
confidence: 99%
“…Moreover, LinkedIn is used to communicate across space, access updated knowledge and offer jobs to needful people (Ellison et al, 2007;Keane et al, 2017). Yearworth and White (2018) noted that social media-driven collaborative awareness campaigns enhance their performance in terms of community empowerment and citizenship behavior.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Online value co-creation through online communities has been explored in different disciplines (Barrett et al, 2016;Yan et al, 2016), however, little is known about the role of online communities as the facilitator of SE's value co-creation to address their challenges. Furthermore, during the last years, SEs have used Information and Communication Technologies (online communities and digital platforms) for different purposes such as marketing (Mitchell et al, 2015), scaling up (Braund & Schwittay, 2016), and communication amongst social enterprise employees (Keane et al, 2017). However, the main focus of these cases has not been on value co-creation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Links between social integration and social enterprise workspaces are poorly understood, and lack empirical assessment (Keane et al., ). We applied mixed methods to explore how relations within a social enterprise contribute to social integration.…”
Section: Introductionmentioning
confidence: 99%